Data Risks in Online Classroom Platforms: A Comparative Analysis of Policy Documents - Le, Thu Thi Kim; Stewart, Bonnie (Journal of Teaching and Learning, 2026)
Online video conferencing platforms are now key classroom tools worldwide, following the emergency remote teaching (ERT) response to COVID-19. However, the data risks and privacy issues these tools pose continue to be addressed only minimally by researchers, educators, and students. Moreover, while the ERT online pivot experience was generally global, digital classroom tools and their provenance vary. Many are developed in the United States and used in other countries and jurisdictions. Yet alternate educational technology markets exist in the contemporary world, though Western claims about educational technologies and privacy tend to centre American technologies. This paper seeks to disrupt the trend of global claims based on regional realities and, instead, to provide a direct comparison of privacy policies of two tools from separate markets: Zoom, developed in the United States, and ClassIn, developed in China. The paper compares the terms of service (ToS) and data risks associated with these two online classroom platforms. The findings ultimately suggest that although distinctions exist between the two in terms of data transparency, safety, security, protection, rights, and contexts, the data privacy implications of Zoom and ClassIn are more similar than different. Implications for educational technology companies, institutions, and educators’ teaching and learning practices are discussed.